Online Learning and Opera: The Rise in Digital Vocal Master Classes and Workshops - Li, Weiyi (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2025)
Professionalism in opera singing depends on the quality of education. This study examines the teaching of opera singing online via master classes and seminars. Based on the present findings, master classes are effective in improving the voice technically and range-wise, whereas seminars are effective in helping opera singers achieve emotionality. These instructional methods were compared in terms of content variety, balance between theoretical and practical components, and their effect on performance artistry and technical skills. Those learning to sing opera through master classes reported experiencing improvements in memory (24%) and problem-solving (22%). Students who attended the online seminars reported improvements in concentration (28%) and memory (26%). Challenges include limited control over assignments, attendance, and assessment. This study highlights effective tools for online opera training, with potential for future comparisons of methods in developing vocal and instrumental skills.